Migration: solid nations and liquid transnationalism? The EU's struggle to find a shared course on African migration 1999-2019 - Irene Schöfberger (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
The European Union (EU) has been struggling to find a shared course on African migration since the entry into force of the Schengen Agreement (1995). It has done so through two interrelated processes of negotiation. Firstly, parties have negotiated narrative frames about migration and, in particular, whether migration should be interpreted in terms of security or in terms of development. Secondly, they have negotiated internal and external migration policies , that is, how migration should be managed respectively inside the EU (based on cooperation between EU member states) and outside it (based on cooperation with third states). In times in which narrative frames increasingly shape policy negotiations, it becomes very important to analyse how policymakers negotiate narrative frames on migration and how these shape policy responses. However, such an analysis is still missing. This discussion paper investigates how European states and institutions have negotiated the relation between EU borders and African mobility between 1999 and the beginning of 2019. It focusses in particular on how the process of negotiation of migration policies has been interrelated with a process of negotiation of narrative frames on migration. It does so based on an analysis of EU policy documents from 1999 to 2019 and on interviews with representatives of European and African states and regional organisations. Two major trends have characterised related EU negotiation processes: migration-security narrative frames have strengthened national-oriented and solid borders-oriented approaches (and vice versa), and migration-development narrative frames have strengthened transnational-oriented and liquid borders-oriented approaches (and vice versa). Since 1999, the European Council has mostly represented security- and national-oriented approaches, and the European Commission has mostly represented development- and transnational-oriented approaches. The two competing approaches have always been interlinked and influenced each other. However, in the last years, security-oriented national and solid border approaches have gained prominence over development-oriented transnational and liquid border approaches. In particular, the Commission has progressively mainstreamed national objectives in its transnational actions and security concerns in its development measures. Prioritising security over transnational development has augmented inequalities, in particular at the expenses of actors with scarce political representation in Africa and the EU. Such inequalities include increasing migrant selectivity and wage dumping.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Flucht und Migration